Faktor-Faktor yang Mempengaruhi Withdrawal Behaviors pada Karyawan Perusahaan Jasa di Jakarta - Putri, Efysastiana; Berliyanti, Dita Oki (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to analyze the effects of Surface Acting and Sexual Harassment on Withdrawal Behavior, mediated by Emotional Exhaustion. The respondents consisted of 230 hotel employees in Jakarta, the majority of whom were women aged 18-24 years, with a high school education or equivalent, and work experience ranging from less than 1 year to 5 years. Of the seven hypotheses tested, six were supported, and one was not. The results showed that Sexual Harassment had a positive and significant effect on Withdrawal Behavior, while Surface Acting had no effect on Withdrawal Behavior. Additionally, both Sexual Harassment and Surface Acting had a positive effect on Emotional Exhaustion, which, in turn, impacted Withdrawal Behavior. Emotional Exhaustion was found to be a full mediator in the relationship between Sexual Harassment and Withdrawal Behavior, as well as between Surface Acting and Withdrawal Behavior. These findings highlight the critical role of Emotional Exhaustion in explaining the relationship between workplace stress factors and withdrawal behavior.